Genetic variability during four cycles of recurrent selection in rice - de Morais Júnior, Odilon Peixoto; Melo, Patrícia Guimarães Santos; de Morais, Orlando Peixoto; Colombari Filho, José Manoel (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to estimate genetic and phenotypic parameters among progenies of the CNA6 population of upland rice (Oryza sativa) for grain yield and plant height in four cycles of recurrent selection, in order to evaluate the genetic variability and the genotype × location interaction. The experimental data were obtained from yield trials of S0:2 progenies, which were carried out in the experimental design of Federer’s augmented blocks, without replications for progenies within each location. The effect of S0:2 progenies was significant in all cycles for grain yield and in the first three cycles for plant height, indicating the maintenance of the population’s genetic potential to generate transgressive progenies. The participation of the component of the progeny × location interaction in phenotypic variance was of high magnitude. The genetic variability of the CNA6 population of upland rice is maintained for grain yield and plant height during the four cycles of recurrent selection.